New N = 2 superconformal field theories from S -folds - Giacomelli, S; Meneghelli, C; Peelaers, W (Springer, 2021)
We study the four-dimensional N = 2 superconformal field theories that describe D3-branes probing the recently constructed N = 2 S-folds in F-theory. We introduce a novel, infinite class of superconformal field theories related to S-fold theories via partial Higgsing. We determine several properties of both the S-fold models and this new class of theories, including their central charges, Coulomb branch spectrum, and moduli spaces of vacua, by bringing to bear an array of field-theoretical techniques, to wit, torus-compactifications of six-dimensional N = (1, 0) theories, class S technology, and the SCFT/VOA correspondence.